International business : challenges and choices - Sitkin, Alan.; Bowen, Nick (Lecturer) (Oxford [England] ; New York : Oxford University Press, 2010)
"What is international business? How much risk is involved in trading across borders? Why is corporate social responsibility important? What impact has the credit crunch of 2008 had on international business? How does a coffee bean grown in Brazil become an espresso sold in Europe? In today's increasingly connected world, international business plays an integral role in day-to-day life. This introductory textbook offers a refreshingly critical approach to international business, examining both good and bad practice and encouraging readers to question and challenge classic assumptions and theories. Drawing on a range of vivid case examples and insights from small businesses to large multinational companies, readers are provided with a realistic depiction of the challenges and opportunities international business can present. Importantly, this book adopts a truly international approach and includes an abundance of examples from countries across the globe, particularly Brazil, Russia, India and China. Online Resource Center and DVD For lecturers: DVD featuring video clips of international business practitioners from the textbook Instructor's manual Additional case studies Test-bank of questions Seminar and discussion questions Ideas for oral presentations Project tasks PowerPoint slides Additional content, carefully integrated with the textbook, to expand students' knowledge Case study questions and indicative answers For students: Interactive Map Online glossary of terms Guidance on critical skills thinking Self-test multiple-choice questions Key websites Revision tips Additional case studies Additional content, carefully integrated with the textbook, to expand students' knowledge Case study questions and answers"--Provided by publisher.
Includes bibliographical references and index.
Keywords: International business enterprises; International business enterprises -- Management